Conductance of Sodium Nitrate in Methanol –Water Mixtures at Different Temperatures - Bhattarai, Ajaya; Sapkota, Deepak; Subedi, Netra P; Khanal, Manoj; Niraula, Tulsi P (Nepal Journal of Science and Technology, 2012)
Precise measurements on the conductivity of Sodium nitrate in methanol-water mixed solvent media containing 0.10, 0.20, 0.30 and 0.40 volume fractions of methanol at 308.15, 318.15 and 323.15 K are reported. The concentrations were varied from (0.001 to 0.15) mol.L-1. The results showed a sharp increase in the conductivity with increasing electrolyte concentration. Also, the conductivity of electrolyte increases with increase in temperature whereas the conductivity of electrolyte decreases with increase in the amount of methanol. DOI: http://dx.doi.org/10.3126/njst.v12i0.6498 Nepal Journal of Science and Technology 12 (2011) 187-92